THE ROLE OF A DIRECT COMMUNICATION CHANNEL BETWEEN PATIENT/FAMILY AND THE TRANSPLANT TEAM - ASS Ibanez; CM Lustosa; CMM Parrode; LL Quintino; LDS Domingues; MGAD Matos; G Zamperlini; RV Gouveia; VC Ginani; A Seber (Hematology, Transfusion and Cell Therapy, 2023)
Introduction: Hematopoietic Stem Cell Transplantation (HSCT) is a complex procedure in which patients and their families are faced with several challenges. The patient/family need constant support and clarification of the entire HSCT process. The contact with the professionals through fix telephone numbers and/or e-mail can be very challenging. Many issues can also be resolved with direct communication instead of transportation to the medical center, that is expensive and time consuming. Communication strategies between patient/family and team can help in the early management of patient/family needs. WhatsApp is the most popular instant messaging social network among Brazilians and completely free if used with an open Wi-Fi access. In October, 2021, a new communication tool was implemented in the HSCT service, a cellular telephone with WhatsApp that is used daytime by nurse practitioners and at night by one of the attending physicians. All patients and their families have direct access to the team through this WhatsApp number. Objective: To analyze the use of the “on-call WhatsApp”by patients and by the healthcare team in all stages of HSCT. Method: Retrospective analysis of all contacts made by the patients/families. Results: From October 09, 2021 to March 16, 2023, 451 contacts were made through our WhatsApp: 68% of the messages were from patient/family, 28% from the team to patient/family and 4% from the physician referring the patient to the HSCT service. The reasons for contact of patients/families were 52 (12%) HSCT-related complications, 32 (7%) medical appointment, 29 (6%) requests summary, 21 (5%) clarification about medications, 20 (4%) about post-HSCT vaccination, 19 (4%) about test results, 15 (3%) about COVID PCR, 14 (3%) request of prescriptions, 12 (3%) questions regarding pre-HSCT, 11 (2%) regarding the donor, 11 (2%) regarding the insurance, and 11 (2%) regarding the Respiratory Unit. The most common symptoms reported using the WhatsApp were gastrointestinal 15 (29%): diarrhea, vomiting, nausea, abdominal pain and inappetence. All patients who sent messages had and answer from the team for prompt management of the clinical problems. Conclusion: This is an excellent option for prompt communication with the patients, avoiding several unnecessary visits. Patients, physicians and nurse practitioners continuously use the “on-call WhatsApp”pre and post appointments. It is also a very valuable tool to reach out patients for the post-HSCT follow-up.